A Covid-19 entre os Magütagü da Amazônia - da Costa Felipe, Yuri (Instituto de Ciências Sociais da Universidade de Brasília, 2021)
This article deals with the experiences thas my people Magütagü lived throughthe COVID-19 pandemic. I bring two situations, in the first situation, I dealwith the death by COVID-19 of a Magüta teacher who lives in a Magütagücommunity in the city of Manaus. In the second situation, I deal with the way acommunity in the Indigenous Land is experiencing COVID-19. Self-care, defined as the practices developed by my people, of ancient knowledge for thepreservation of their health, is triggered and used at this time when indigenoushealth policies and services are weakened